Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Kiều Nguyễn Linh Ánh

a) (2x - 1)2 - (2x + 5)(2x + 1) = 10

b) 92 (x - 1) + 25 .(1 - x) = 0

c) x+ 3x - 4 = 0

『Kuroba ム Tsuki Ryoo...
20 tháng 8 2023 lúc 11:38

`#040911`

`a)`

`(2x - 1)^2 - (2x + 5)(2x + 1) = 10`

`\Leftrightarrow 4x^2 - 4x + 1 - (4x^2 + 12x + 5) = 10`

`\Leftrightarrow 4x^2 - 4x + 1 - 4x^2 - 12x - 5 = 10`

`\Leftrightarrow (4x^2 - 4x^2) - (4x + 12x) + (1 - 5) = 10`

`\Leftrightarrow -16x - 4 = 10`

`\Leftrightarrow -16x = 10 + 4`

`\Leftrightarrow -16x = 14`

`\Leftrightarrow x = \dfrac{-7}{8}`

Vậy, `x= \dfrac{-7}{8}`

`b)`

`9^2(x - 1) + 25(1 - x) = 0`

`\Leftrightarrow 9^2(x - 1) - 25(x - 1) = 0`

`\Leftrightarrow (x - 1)(9^2 - 25) = 0`

`\Leftrightarrow`\(\left[{}\begin{matrix}x-1=0\\9^2-5^2=0\end{matrix}\right.\)

`\Leftrightarrow`\(\left[{}\begin{matrix}x=1\\\left(9-5\right)\left(9+5\right)=0\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=1\\4\cdot14=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=1\\56=0\left(\text{vô lý}\right)\end{matrix}\right.\\ \text{Vậy, x = 1}\)

`c)`

\(x^2+3x-4=0\)

`\Leftrightarrow x^2 + 4x - x - 4 = 0`

`\Leftrightarrow (x^2 - x) + (4x - 4) = 0`

`\Leftrightarrow x(x - 1) + 4(x - 1) = 0`

`\Leftrightarrow (x + 4)(x - 1) = 0`

\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x-1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-4\\x=1\end{matrix}\right.\\ \text{ Vậy, }x\in\left(-4;1\right)\)


Các câu hỏi tương tự
Kiều Thị Ngọc Ánh
Xem chi tiết
iu
Xem chi tiết
Pham Trong Bach
Xem chi tiết
12	Mai Linh Giang
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Cao Ngọc Kỳ
Xem chi tiết
Hânn Nguyễn
Xem chi tiết
lNkhánh
Xem chi tiết